Stereotactic Radiosurgery for Olfactory Groove Meningiomas: An International, Multicenter Study. Issue 5 (12th August 2021) - Bunevicius, Adomas; Ahn, Jungeun; Fribance, Sarah; Peker, Selcuk; Hergunsel, Batu; Sheehan, Darrah; Sheehan, Kimball; Nabeel, Ahmed M; Reda, Wael A; Tawadros, Sameh R; Abdelkarim, Khaled; El-Shehaby, Amr M N; et al.
Abstract: BACKGROUND: Stereotactic radiosurgery (SRS) is increasingly considered for selected olfactory groove meningiomas (OGMs). OBJECTIVE: To investigate the safety and efficacy of SRS for OGMs. METHODS: From 20 institutions participating in the International Radiosurgery Research Foundation, we pooled patients who underwent SRS for histologically confirmed or radiologically suspected WHO grade I OGMs and were followed for 6 mo or more after the SRS. RESULTS: In total, 278 (median age 57 yr) patients underwent SRS for histologically confirmed (29%) or radiologically suspected (71%) WHO grade I OGMs Median treatment volume was 4.60 cm 3 (range: 0.12-27.3 cm 3 ), median prescription dose was 12 Gy, and median dose to the olfactory nerve was 11.20 Gy. During median post-SRS imaging follow-up of 39 mo (range: 6-240 mo), 43% of patients had partial or marginal response, 54% of patients had stable disease, and 3% of patients experienced progression. During median post-SRS clinical follow-up of 51 mo (range: 6-240 mo), 36 (13%) patients experienced clinical and/or radiological adverse radiation events (AREs). Elevated risk of AREs was associated with larger OGM volume ( P  = .009) and pre-SRS peritumoral T2/fluid-attenuated inversion-recovery signal abnormalities ( P  < .001). After the SRS, olfaction remained stable, improved, or deteriorated in 90%, 8%, and 2% of patients, respectively. Complete post-SRS anosmia was predicted by partial/complete anosmia before the SRS (odds ratio [OR] = 83.125; 95% CI [24.589-281.01], P  < .001) and prior resection of OGM (OR = 3.919; 95% CI [1.713-8.970], P  = .001). CONCLUSION: SRS is associated with durable local control of the majority of OGM patients with acceptable safety profile. SRS allows preservation or improvement of olfactory function in the majority of OGM patients. Graphical Abstract: